Romidepsin is effective and well tolerated in older patients with peripheral T-cell lymphoma: analysis of two phase II trials. Issue 10 (3rd October 2017) - Shustov, Andrei; Coiffier, Bertrand; Horwitz, Steven; Sokol, Lubomir; Pro, Barbara; Wolfson, Julie; Balser, Barbara; Eisch, Robin; Popplewell, Leslie; Prince, H. Miles; Allen, Steven L.; Piekarz, Richard; et al.
Abstract: Peripheral T-cell lymphomas (PTCLs) are a rare group of lymphoid neoplasms with high relapse rates after initial therapy and poor prognosis. Most patients are aged ≥60 years and are often not candidates for aggressive salvage therapies. Romidepsin, a potent class I histone deacetylase inhibitor, has shown significant single-agent activity in relapsed/refractory PTCL. We evaluated the efficacy and tolerability of romidepsin in elderly patients in this setting. Ninety-five patients aged ≥60 years were identified from 2 prospective phase 2 registration trials of romidepsin, and comparative analyses were performed with younger patients from these trials. Response rates, progression-free survival, and overall survival were not statistically different for younger vs older patients. The toxicity profile in older and younger patients was similar in both trials. Romidepsin demonstrated similar efficacy and tolerability in younger and older patients and presents an attractive treatment option for relapsed/refractory PTCL regardless of age. Trial registration: Clinicaltrials.gov identifiers: NCT00426764, NCT00007345.